Hospitalidade na educação infantil: o acolhimento e a participação dos pais na gestão democrática escolar - MACIEL, Andreza dos Santos (2016)
The objective of this study is to understand the relationship of welcome and hospitality in the dynamics of reception parents held a school unit as a factor of change in the relationship between the group of parents of students and the school itself, the school democratic management. For the study left is a literature on hospitality and host school democratic management and family-school relations, with the object of study one school unit Childhood Education located in the north of São Paulo. Thus, the question posed is to understand how the host can be considered a factor that allows the participation of parents in school democratic management. The study is characterized as exploratory and descriptive qualitative, based on documentary and field research, using semi-structured interviews from the focus group technique, carried out with parents, teachers and school managers, in order to understand the perception of parents and managers of dynamic proposals with a view to democratic school management. As a result, there was a greater community participation, concluding that the actions proposed represent a differential in the relationship between school and community from the social interaction, which provides creation of linkages in participatory and democratic management.